Knowledge, Attitude and Practice on Healthy Diet among Mothers Feeding Their Children: An Urban School Based Study in Dhaka, Bangladesh - Shahrin, Tunazzina; Paul, Bijoy Kumer; Islam, Tauhidul; Jahan, Nusrat; Nusrat, Farzana; Rahman, Moyeedur; Hasan, Md (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Research revealed that daily diet of school going children are still inadequate in nutrition with less consumption of fruits and vegetables and higher consumption of junk foods that are rich in fats, salt, and sugar. Those phenomena are related to mothers’ knowledge, attitude, and practice on healthy diet. Objective: To determine knowledge, attitude, and practice on healthy diet among mothers feeding their school going children. Methods: This cross-sectional study was conducted between January and December of 2018 in some randomly selected schools under Dhaka City Corporation, Bangladesh. We adopted convenient sampling technique. A total of 120 mothers participated in this study who had school going children aged between six and eight years. A pretested, semi-structured questionnaire was used for data collection. The participants chose Bangla version for filling up the survey questionnaire. A modified Likert’s scale was used. Results: Among the participants, 70(58.2%) were in 30-35 years and 50(41.8%) were in 36-40 years age group. All the mothers know the importance of feeding healthy food to the child; however, 72.5% could not mention specific description of constituents of a healthy diet. 89.2% of mothers have somehow control over her own food habit. Only 5.8% mothers learned new healthy cuisine in the previous week.54.2% visited market at least once a week, while23.3% mothers did not buy any fruits or vegetables, only 5.8% had grown and eaten from own gardens.14.2% kept their children with them while cooking to show how healthy meal can be prepared.In the previous week, 14.2% of children took no fruits, 34.2% took 0.5 cup amount, 43.3% took one cup, 8.3% took two cups per day, while 12.5% children did not take any vegetables, 31.7% took 0.5 cup, 44.2% took one cup, 11.7% took two cups of vegetables per day. 11.7% children did not take any sugary drinks, 67.5% took one cup, 20.8% took two cups of sugary drinks per day in the previous week. 87.5% children did not visit market for at least once a weekand their mothers did not encourage them to buy any fruit or vegetables. 97.5% mothers did not measure any calories and nutritional status over the week; however, only 2.5% measured at least once. None of the mothers cooked any healthy food at home. Only 17.5% of the mothers had discussion about eating fruits and vegetables. According to the respondents, 65% encouraged their children 21 times healthy feeding practice over the last week, 33.4% had 14-20 times and 1.6% less than 14 times in the previous week. Conclusion:Our study revealed that many mothers cannot define well what constitutes a healthy meal. They hardly cook healthy meal for their children and do not encourage them to eat fruits and vegetables. Most of them do not measure daily calories or show any interest to discuss nutritional topics with others. International Journal of Human and Health Sciences Vol. 06 No. 04 Oct’22 Page: 398-403